Sistem Informasi Transaksi Penjualan Berbasis Website ( Studi kasus Toko Roti Bakar Pelangi di Semarang ) - Yosita Lianawati; Suyudi Suyudi; Vincentius Ardi P (Universitas Katolik Widya Karya Malang, 2023)
The process of recording sales transactions, which currently still uses manuals through books, creates a lot of risks of data errors and data loss. Toko Roti Bakar Pelangi is an MSME business that operates in Semarang and sells more than 100 pieces every day, with the recording of sales done manually causing many sales report calculation errors. So the authors designed a website-based sales information system that can be used to facilitate recording and preparation of sales reports. The development method used is the prototype method. System design uses UML models such as use case diagrams and class diagrams and activity diagrams. The system is built using the PHP programming language and Mysql database, which is analyzed using White Box, Black Box, Hypothesis Testing, Normalization Testing, Validity Testing, Reliability Testing, and Benefit Testing. The result of the system created is a Website-Based Sales Transaction Information System at Roti Bakar Pelangi Semarang Stores. The purpose of the information system is to produce a system that assists in the process of recording reports at Roti Bakar Pelangi Semarang to make it more efficient.